Effects of multi-mode physical stimulation on APP/PS1 Alzheimer's disease model mice. Issue 12 (December 2022) - Liu, Shupeng; Li, Shuyang; Xia, Yudan; Zhang, Heng; Tian, Jing; Shan, Chunlei; Pang, Fufei; Wang, Ying; Shang, Yana; Chen, Na
Abstract: Some researchers and clinics have reported that non-drug treatments for Alzheimer disease (AD) such as electrical stimulation, light stimulation, music stimulation, laser stimulation, and transcranial magnetic stimulation may have beneficial treatment effects. Following these findings, in this study, we performed multimodel physical stimulation on APP/PS1 mice using visible light, music with a γ rhythm, and an infrared laser. And the effects of physical stimulation on APP/PS1 mice were evaluated by behavioral analysis, the content of amyloid (Aβ40 and Aβ42 ), and NISSL staining of hippocampal tissue slices. The results of subsequent behavioral and tissue analyses showed that the multi-model physical stimulations could relieve APP/PS1 mice's dementia symptoms, such as the behavior ability, the content of Aβ40 and Aβ42 in the hippocampal tissue suspension, and Nissl staining for hippocampal tissue analyses. Abstract : Alzheimer's disease; Amyloid; γ rhythm; APP/PS1; Multimodal physical stimulation.